Comparison of Psychological Well-being in Employed and Non-employed Women in Isfahan - Mehri Shams Ghahfarokhi; Mahmoud Keyvanara; Mohammad Reza Ghasemi (Mazandaran University of Medical Sciences, 2024)
Introduction and purpose: Experts, consider the current Psychological well-being, as a fairly accurate indicator of a person's current health status. The aim of this study was to compare psychological well-being in employed and non-employed women in Isfahan. Methods: This research is applied in terms of purpose, descriptive-analytical, and cross-sectional. The statistical population is all women aged 20 to 60 years in Isfahan in 2021, the number of samples for each employed and non-employed women was 394 which was selected by available sampling method. The standard Warwick and Edinburgh Mental Welfare Questionnaire was used for data collection and SPSS26 software was used for data analysis. Results: The mean ranks and sum of ranks for psychological well-being, positive relationships with others, and energy levels are higher among working women compared to non-working women. Significant differences exist between working and non-working women in these variables, indicating that working women generally experience higher levels of mental well-being, positive relationships, and energy (P≤0.001). However, the mean ranks and sum of ranks for optimism among non-working women are slightly higher than those among working women, although this disparity is not statistically significant (P=0.955). Conclusion: The results show that employed women have better psychological well-being compared to non-employed women in Isfahan. This issue can be used by policy makers to develop appropriate strategies for women's employment. Policymakers and managers of organizations, by identifying and understanding the factors affecting the increase of women's psychological well-being, will be able to use scientific methods to adopt policies to promote women's psychological well-being.